Disruptive mood dysregulation disorder in offspring of parents with depression and bipolar disorder. (June 2017) - Propper, Lukas; Cumby, Jill; Patterson, Victoria C.; Drobinin, Vladislav; Glover, Jacqueline M.; MacKenzie, Lynn E.; Morash-Conway, Jessica; Abidi, Sabina; Bagnell, Alexa; Lovas, David; Hajek, Tomas; Gardner, William; et al.
Abstract : Background: It has been suggested that offspring of parents with bipolar disorder are at increased risk for disruptive mood dysregulation disorder (DMDD), but the specificity of this association has not been established. Aims: We examined the specificity of DMDD to family history by comparing offspring of parents with (a) bipolar disorder, (b) major depressive disorder and (c) a control group with no mood disorders. Method: We established lifetime diagnosis of DMDD using the Schedule for Affective Disorders and Schizophrenia for School Aged Children for DSM-5 in 180 youth aged 6–18 years, including 58 offspring of parents with bipolar disorder, 82 offspring of parents with major depressive disorder and 40 control offspring. Results: Diagnostic criteria for DMDD were met in none of the offspring of parents with bipolar disorder, 6 of the offspring of parents with major depressive disorder and none of the control offspring. DMDD diagnosis was significantly associated with family history of major depressive disorder. Conclusions: Our results suggest that DMDD is not specifically associated with a family history of bipolar disorder and may be associated with parental depression.